Caregivers and people with disabilities: relational embodiment of stigma and concern in Egypt - Omarah, Nahla (AUC Knowledge Fountain, 2020)
This thesis explores disability as a relational model and how stigma is produced within an Egyptian domain. This study focuses not only on People with Disabilities (PWDs) but rather on their primary caregivers i.e. parents and siblings. I examine how stigma affects the relationship between caregivers and their disabled family members. I also explore how some relatives run the risk of being stigmatized themselves by association develop a "stigmaphile response". Thus, exploring the notion of concern that is inevitable in caregiver-PWD relationship and how this embodies individuals into new subjectivities under society's control. Furthermore, this thesis aims at finding a way to combat the stereotypes that arise from being associated with PWDs and also aims at shifting people's perspectives into considering that disability should not be categorized it is too diverse and many aspects which differ from one disability to the other thus cannot be categorized in to a "new gender". My goal is to help find a way to eradicate the "shame" that surrounds the word "disability" in order for individuals to be able to enjoy a quality of life without fear, blame and exclusion.